Analyzing the Influence of Fundamental and Non-fundamental Factors on the Indonesia Stock Exchange (BEI) - Glenn E Kalunda (Institute of Accounting Research and Novation (IARN), 2023)
This research investigates the underpricing of Initial Public Offerings (IPOs) on the Indonesia Stock Exchange (BEI), focusing on the influence of fundamental and non-fundamental factors. By analyzing a comprehensive dataset of IPOs, including firm-specific characteristics, market conditions, and underwriter reputation, this study aims to uncover the determinants and implications of underpricing dynamics in the context of emerging markets. The analysis reveals significant insights into the factors driving IPO underpricing on the BEI. Fundamental factors such as firm size, profitability, and industry affiliation exert a notable influence on underpricing, with larger, more profitable companies experiencing lower levels of underpricing compared to smaller firms operating in nascent industries. Non-fundamental factors such as market sentiment, investor demand, and underwriter reputation also play a significant role in shaping underpricing dynamics, amplifying market dynamics and influencing pricing outcomes. The findings of this research have practical implications for investors, issuing companies, regulators, and market participants. By informing pricing strategies, enhancing investor confidence, and improving market efficiency, this research empowers stakeholders to navigate the complexities of the IPO market more effectively and capitalize on investment opportunities. Looking ahead, future research should continue to explore new avenues of inquiry and refine existing models to further our understanding of IPO underpricing dynamics and facilitate value creation in capital markets.